Digitisation, Big Data, and the Future of the Medical Humanities/Text-Mining and the History of Medicine: Big Data, Big Questions? - Toon, Elizabeth; Timmermann, Carsten; Worboys, Michael (Medical History, 2016)
The article presents the authors' views on their experience of embarking on a collaborative project to develop a search engine for medical history. The project involves the use of text mining tools to search for high quality data by analyzing patterns and trends. The project was sponsored by British nonprofit UK Arts and Humanities Research Council and conducted in partnership with the National Centre for Text Mining.